PENGARUH RASIO KEUANGAN DAN FIRM SIZE TERHADAP RETURN SAHAM LQ45 PADA MASA PANDEMI COVID-19 - Zidni Maziyyah (Jurnal Ilmu Manajemen, 2022)
This study is to determine the impact of the current ratio, earning per share, and firm size during the COVID-19 pandemic. This research case study focuses on LQ45 emitens’ index on 2020. This is quantitative research with an associative approach. The population of this study consists of 45 companies with ten companies as samples that are selected using purposive sampling technique. The data analysis method for this study uses SPSS 20 software. The results show that the current ratio has no causality effect on stock return. A high value of current ratio not only illustrates the company’s strong liquidity position, but can also indicate inefficient use and management of cash and other short-term assets. Earning per share does not affect the stock return. High EPS does not necessarily reflect the effectiveness of good company management, this is because the cost of capital is not calculated in obtaining net profit after tax. In addition, the dividend is not necessarily only determined by the value of EPS because many factors are considered through the general meeting of shareholders. Firm size does not affect the stock return. Large companies with high total assets will tend to invest more capital. In a stable economic condition, profits will tend to increase. However, in crisis conditions, large companies tend to have large operating costs so that they have the potential to burden the company and decrease return. Therefore, large companies do not necessarily provide large stock returns for their investors, and vice versa.